THE EFFECT OF PROJECT BASED LEARNING MODEL ON COGNITIVE SKILL OF 8th GRADE STUDENTS’ ON HUMAN CIRCULATORY SYSTEM TOPIC - Difa Aulya Syahmi; Rahmah Evita Putri (Universe, 2023)
Students’ learning activities that are hard to recognite by students give an impact on enthusiastic about learning. It is necessary to adjust a variety of learning, to increase the cognitive skill of students such as the Project Based Learning model. This study aims to determine the effect of the Project Based Learning model on the cognitive skill of 8th grade students on human circulatory system topic. The research method used Quasi Experiment with Non-equivalent Post Test Only Control Group Design. Samples were taken using a purposive sampling technique, so 64 students were selected. Data collection was carried out by giving post test questions. The data obtained were analyzed using the Normality Test, Homogeneity Test, and t Test. The results of the analysis showes that the average cognitive skill of the experimental class is 79.68 and the average cognitive sklill of the control class is 53.84. Based on the t test obtained Tcount is 5.96 and Ttable is 1.6698 with a significant level of 0.025. The results shows Tcount > Ttable so that H0 is reject and Ha is accept. It can be concluded that there is an effect of the Project Based Learning model on the cognitive skill in 8th grade on the human circulatory system topic.